Peningkatan Kemampuan Manajerial Kepala Madrasah dalam Mengembangkan Budaya Sadar Literasi Bagi Guru dan Peserta Didik - Idan Nurdiana (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
The purpose of this study is to ascertain whether madrasah principals have improved managerial skills in creating a literacy-aware culture for instructors and students. School Action Research is the technique applied in this study. There were two cycles for the research. Twenty teachers and 21 samples of students in class XI-A served as the samples. Researchers rely on information from their colleagues, students, and teachers. Action planning, implementation, observation, reflection and assessment, problem-solving, and conclusions are all part of the action research process. Techniques for gathering data are based on qualitative data analysis of primary and empirical data. The procedure of gathering data through observation, questionnaire, discussion, and interviews. The results of the study showed that the managerial ability of the madrasah principal in the initial observation of the first cycle obtained a score of 79.75, while in the second cycle a score of 95.31% was obtained. The POACE ability of the head in developing the program in the first cycle reached 75%, while in the second cycle a score of 93.75 was obtained. The results of the study prove that there is an increase in the managerial ability of the madrasah principal in developing a literacy awareness culture program for teachers and students.